Effect of oral citrulline supplementation on whole body protein metabolism in adult patients with short bowel syndrome: A pilot, randomized, double-blind, cross-over study. Issue 6 (December 2019) - Jirka, Adam; Layec, Sabrina; Picot, Denis; Bernon-Ferreira, Silvia; Grasset, Nadège; Flet, Laurent; Thibault, Ronan; Darmaun, Dominique
Summary: Background & aims: As citrulline is produced by small intestine, plasma citrulline concentration is decreased and may become essential in patients with short bowel syndrome (SBS). In a rat model of SBS, citrulline supplementation enhanced muscle protein synthesis. The aim of the study was to determine whether citrulline impacts whole body protein metabolism in patients with SBS. Methods: Nine adults with non-malignant SBS (residual small bowel 90 ± 48 cm; mean ± SD) who were in near-normal nutritional status without any artificial nutrition, were recruited long after surgery. They received 7-day oral supplementation with citrulline (0.18 g/kg/day), or an iso-nitrogenous placebo in a randomized, double-blind, cross-over design with a 13-day wash-out between regimens, and an intravenous 5-h infusion of L-[1– 13 C]-leucine in the postabsorptive state to assess protein metabolism after each regimen. Results: Plasma citrulline concentration rose 17-fold (25 ± 9 vs. 384 ± 95 μmol/L) and plasma arginine 3-fold after oral citrulline supplementation (both p < 4 × 10 −6 ). Supplementation did not alter leucine appearance rate (97 ± 5 vs. 97 ± 5 μmol kg −1 .h −1 ; p = 0.88), leucine oxidation (14 ± 1 vs. 12 ± 1 μmol kg −1 .h −1 ; p = 0.22), or non-oxidative leucine disposal (NOLD), an index of whole-body protein synthesis (83 ± 4 vs. 85 ± 5 μmol kg −1 .h −1 ; p = 0.36), nor insulin or IGF-1 plasma concentrations. In each of the 3 patients with baseline citrulline<20 μmol/L, citrulline supplementation increased NOLD. Among the 7 patients with plasma citrulline <30 μmol/L, the effect of supplementation on NOLD correlated inversely (r 2  = 0.81) with baseline plasma citrulline concentration. Conclusion: 1) Oral citrulline supplementation enhances citrulline and arginine bioavailability in SBS patients. 2) Oral citrulline supplementation does not have any anabolic effect on whole body protein metabolism in patients with SBS in good nutritional status, in the late phase of intestinal adaptation, and with near-normal baseline citrulline homeostasis. 3) Whether oral citrulline would impact whole body protein anabolism in severely malnourished SBS patients in the early adaptive period, and with baseline plasma citrulline below 20 μmol/L, warrants further study. Registered under ClinicalTrials.gov Identifier no. NCT01386034 .